From despair to faith : the spirituality of Soren Kierkegaard - Barnett, Christopher B. (Fortress Press, 2014)
Soren Kierkegaard has been called many things, from brooding genius and "melancholy Dane" to the father of existentialism. Yet, rather than clarify the nature of Kierkegaard's writings, such labels have often obscured other important aspects of his authorship. Such, indeed, is the case with Kierkegaard's standing as a spiritual author. In From Despair to faith: The Spirituality of Soren Kierkegaard, Christopher B. Barnett endeavors to remedy this problem.